The Associations Between Helicobacter pylori Infection, Serum Vitamin D, and Metabolic Syndrome: A Community-Based Study. Issue 18 (May 2016) - Chen, Li-Wei; Chien, Chih-Yi; Hsieh, Chia-Wen; Chang, Liang-Che; Huang, Mei-Huei; Huang, Wen-Yuan; Kuo, Sheng-Fong; Chien, Cheng-Hung; Lin, Chih-Lang; Chien, Rong-Nan
Abstract : Abstract: The associations between Helicobacter pylori infection, serum vitamin D level, and metabolic syndrome (MS) are controversial. The present community-based study aimed to investigate the effect of H pylori infection and serum vitamin D deficiency on MS development. Individuals from the northeastern region of Taiwan were enrolled in a community-based study from March, 2014 to August, 2015. All participants completed a demographic survey and underwent the urea breath test (UBT) to detect H pylori infection as well as blood tests to determine levels of vitamin D, adiponectin, leptin, and high-sensitivity C-reactive protein. The ATP III criteria for MS were used in this study. A total of 792 men and 1321 women were enrolled. The mean age was 56.4 ± 13.0 years. After adjusting for age and sex, the estimated odds of MS development for a UBT-positive subject were 1.503 (95% confidence interval [CI]: 1.206–1.872, P < 0 .001) when compared to a UBT-negative subject. For participants with vitamin D deficiency (<20 ng/mL), the odds of MS development were 1.423 (95% CI: 1.029–1.967, P = 0 .033) when compared to those with sufficient vitamin D level (>30 ng/mL). For participants with both H pylori infection and vitamin D deficiency, the odds of MS development were 2.140 (95% CI: 1.348–3.398, P = 0 .001) when compared to subjects without H pylori infection and with sufficient vitamin D levels. H pylori infection and vitamin D deficiency could be predictors of MS. For individuals with both H pylori infection and vitamin D deficiency, the odds of MS development were 2.140 when compared to individuals without H pylori infection and with sufficient vitamin D levels.